2014
DOI: 10.1352/1944-7558-119.6.496
|View full text |Cite
|
Sign up to set email alerts
|

Residential Transitions Among Adults With Intellectual Disability Across 20 Years

Abstract: The present study addresses critical gaps in the literature by examining residential transitions among 303 adults with intellectual disability over 10 years (Part 1) and 75 adults with Down syndrome over 20 years (Part 2). All adults lived at home at the start of the study, but many moved to a variety of settings. Several characteristics of the adults with intellectual disability differed across settings, most notably adaptive behavior and the number of residential transitions, while characteristics such as ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 43 publications
2
34
2
2
Order By: Relevance
“…Prior research suggests a selection mechanism whereby healthy adults (as opposed to less healthy) adults with ID are less likely to be moved from family homes to residential accommodation (Woodman et al . ) which would suggest that people with diabetes are more likely to transfer to residential settings. Finally, our findings may reflect a lack of testing for diabetes in family households.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests a selection mechanism whereby healthy adults (as opposed to less healthy) adults with ID are less likely to be moved from family homes to residential accommodation (Woodman et al . ) which would suggest that people with diabetes are more likely to transfer to residential settings. Finally, our findings may reflect a lack of testing for diabetes in family households.…”
Section: Discussionmentioning
confidence: 99%
“…Training aids like metronomes 20,21 and popular songs, 22,23 as well as repetitive retraining 24 might be helpful in this sense. Although no prior studies have been carried out to test this hypothesis, having in mind the psychological as well as the learning and training characteristics of DS people, 25 we consider that songs and other fun and focused strategies might improve CC quality and would be welcome by youngsters with DS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research supports the use of interventions to improve the independent living skills of students with ASD and ID with the ultimate goal of increasing the likelihood of better adult outcomes (i.e., Klinger et al, 2015;Liss et al, 2001;Taylor & Mailick, 2013;Woodman et al, 2014). Moreover, students with ASD and ID are at risk for becoming reliant on adults around them to complete independent living skills (Giangreco & Broer, 2007), which can lead to dependency on prompting and assistance (Koegel & Egel, 1979).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…For example, Woodman, Mailick, Anderson, and Esbensen (2014) found that individuals with ID who had higher levels of adaptive behavior were more likely to live semi-independently or independently. Also, a recent study by Klinger, Klinger, Mussey, Thomas, and Powell (2015) showed that poor adaptive behavior in individuals with ASD was the strongest predictor of unemployment, social isolation, depression, and lower overall quality of life in adulthood.…”
Section: Introductionmentioning
confidence: 99%